A field study on thermal comfort and adaptive behaviour of university open-plan offices in severe cold regions of China - Hongrui Zhang; Cheng Sun; Luchen Zhang; Bin Yan; Ying Liu; Qi Dong (Journal of Asian Architecture and Building Engineering)
This study investigates the thermal comfort and adaptive behaviours of occupants in open-plan office spaces at a university located in Northeast China, a region characterized by severely cold winters with an average temperature ≤−10°C in the coldest month. The research focuses on the interaction between buildings and occupants from an indoor environmental quality perspective, contributing to the field of occupant-centric building design and operation by studying thermal comfort, adaptive behaviour, and energy-efficient heating strategies in severe cold regions. By employing field measurements and a subjective questionnaire survey, we summarized the environmental factors contributing to thermal discomfort and their respective weights. The results reveal that air temperature, radiant asymmetry caused by envelopes, and relative humidity are the three most significant factors, with weights of 0.376, 0.209, and 0.194, respectively. Furthermore, a fuzzy comprehensive evaluation method was employed to determine the thermal neutral operating temperature (22.5°C) and the acceptable operating temperature range (19.5°C to 25.5°C). Based on the analysis of occupant behaviour characteristics and preferences, a suitable winter heating setting is proposed for open-plan university offices. These findings support the development of more accurate building performance simulations and inform strategies for low-energy building management in severe cold regions.